Higher-order Iterative Learning Control Law Design using Linear Repetitive Process Theory: Convergence and Robustness. Issue 1 (July 2017) - Wang, Xuan; Chu, Bing; Rogers, Eric
Abstract: Iterative learning control has been developed for processes or systems that complete the same finite duration task over and over again. The mode of operation is that after each execution is complete the system resets to the starting location, the next execution is completed and so on. Each execution is known as a trial and its duration is termed the trial length. Once each trial is complete the information generated is available for use in computing the control input for the next trial. This paper uses the repetitive process setting to develop new results on the design of higher-order ILC control laws for discrete dynamics. The new results include conditions that guarantee error convergence and design in the presence of model uncertainty.